An approach for spasticity quantification based on the stretch reflex threshold - Ferreira, João Amaro Oliveira (2010)
Spasticity is a common and complex motor disorder that affects more than 12 million persons in the world. There are several studies on spasticity quantification in the literature but there is still a need for measurement improvements. This paper presents the design of a mechatronic device for spasticity quantification, in joint of ankle, elbow and knees. This approach is based on the velocity dependent of the tonic stretch reflexes. The relevant variables, the measurement range and the adequate measurement systems are selected. The data acquisition system, board and software, are also defined and tested in laboratory. Next step consists of the system validation in clinical environment.